Dermatological Manifestation of Chronic Kidney Disease - Shrestha, Rima; Basukala, M; Shrestha, D (Journal of General Practice and Emergency Medicine of Nepal, 2014)
Introduction: Dermatological abnormalities are common in chronic kidney disease (CKD) and it can vary from xerosis, pruritus to hyperpigmentation, purpuric skin changes, nail abnormalities.Methods: This is a cross sectional observational study. The objective is to determine the prevalence of skin diseases in chronic kidney disease.Results: Forty-nine patients (30 males and 19 females) were examined. In this study, the commonest presenting symptom was pruritus in 29(59.2%). Pruritus followed by pain in 15(30.6%) and burning sensation in 9(18.4%). Hyperpigmentation was the most common finding in our study. It was followed by xerosis in 17(34.7%), nail changes in 16(32.7%), eczema in 11(22.4%), steroid induced side-effects like acneiform eruptions in 6 patients (4%) and cushingoid facies in 2 patients. Similarly generalized pruritus were noted in 9 cases (18.4%), tinea in 9 patient (18.4%), herpes zoster and verruca in 7 (14.3%each)patients, herpes simplex in 6 patients (12.2%), bacterial infection in 5 and purpura in 5 patients (10.2%each), followed by urticaria in 4 patients (8.2%), SLE(8.2%), DLE in 2(4.1%), erythema nodosum in 4 (8.2%), pityriasis versicolor in 3(6.1%). Nail changes was seen in 16(32%) and included leuconychia in (40%), koilonychia (24%), subungual hyperkeratosis (20%), onycholysis (10%), mees’ lines (4%) and beau’s lines (2%).Conclusion: In our study hyperpigmentation was the most common finding followed by xerosis and nail changes.